Barriers and motivators for postpartum intrauterine contraceptive devices uptake in a rural tertiary care hospital in Maharashtra - Ankita; Kamat, Deepak; Bangal, V. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postpartum family planning is crucial for improving maternal and neonatal health, especially in rural areas with limited healthcare access. Postpartum intrauterine contraceptive devices (PPIUCD) offer a safe, effective, and long-acting contraceptive solution. However, its uptake remains low due to various barriers, including lack of awareness, cultural beliefs, and fear of complications. This study aimed to explore the barriers and motivators influencing PPIUCD uptake among postnatal women in a rural tertiary care center in Maharashtra, India. Methods: A cross-sectional study was conducted from October 2024 to November 2024 at Pravara institute of medical sciences, Loni, Maharashtra. Seven hundred forty postnatal women were randomly selected and interviewed. Statistical analysis was performed using SPSS version 21. Results: The overall acceptance rate of PPIUCD was 37.9%. Acceptance was significantly higher among women with prior knowledge of PPIUCD and those with primary/secondary education. The main reasons for refusal were opting for other contraceptive methods (38.2%), fear of complications (28.7%), and husband’s and relative’s disapproval (21.6%). Women who attended three antenatal care visits were more likely to accept PPIUCD. Conclusions: The study highlights the need for targeted interventions focusing on awareness, partner involvement, and culturally sensitive counselling to enhance PPIUCD acceptance in rural settings. Effective antenatal counselling can address misconceptions and promote informed decision-making.